Analisa Kebutuhan Guru dalam Pengembangan Bahan Ajar Bahasa Inggris untuk Pariwisata - Darmiyani Ni Luh Putu; Pande Agus Adiwijaya; Wedayanthi Luh Made Dwi (Universitas Pendidikan Ganesha, 2022)
This analysis aims to determine the needs of teachers in the development of teaching materials and also the things that support the activities of developing these teaching materials. In addition, this research instrument uses observation, interviews, questionnaires and also documentation. This study uses a qualitative descriptive method. There are 5 stages in this research, namely knowing the potential and problems, literature study and information gathering, product design, design validation, tested design. The subjects in this study were teachers who were responsible for the manufacture and development of these teaching materials. While the object of research is the students who use teaching materials as a guide in the learning process other than the teacher. Based on the research that has been done, the development of teaching materials at SMA Astika Dharma is quite good. In addition to the main book, they use other teaching materials in the form of powerpoints, pictures/illustrations and the use of teaching aids. The students can also follow all the activities well, because of the teaching materials. This teaching material also supports the curriculum used in the high school, namely the 2013 curriculum. The purpose of the 2013 curriculum itself is so that students are able to be more active, creative and innovative than their teachers.